146k views
4 votes
Can someone find the inverse and explain it step to step please!!!!!!! (FOR QUESTION 3)

Can someone find the inverse and explain it step to step please!!!!!!! (FOR QUESTION-example-1

1 Answer

0 votes

Answer:

f^-1(x) = 4(x+5)/3

Explanation:

Let f(x) = y

So, y = (3/4)x - 5

y + 5 = (3/4)x

4(y+5)/3 = x

The steps are first to make a variable that holds the same value as the function, then from there you simplify and eventually make x the subject of the equation.

User Uldall
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.